Pemanfaatan Teknologi Machine Learning Untuk Klasifikasi Wilayah Risiko Kekeringan di Daerah Istimewa Yogyakarta Menggunakan Citra Landsat 8 Operational Land Imager (OLI) - Ayuningtyas, Fajar; Prasetyo, Sri Yulianto Joko (Jurusan Teknologi Informasi Universitas Semarang, 2020)
Drought is a natural disaster that occurs slowly and lasts a long time. Bantul and Gunung Kidul Regencies, Special Region of Yogyakarta are also areas affected by high drought risk. This happened because the area was the result of the construction of a cement factory and limestone mining along the Sewu Mountains. Prediction and classification of areas affected by drought can be done more accurately over large areas by extracting vegetation indices through remote sensing imagery. This research was conducted to provide information about the potential risk of drought in the region using Landsat 8 OLI spectral vegetation index data. Prediction or classification of drought potential using Artificial Neural Network. Vegetation index used in this study is NDVI, TCI, VCI, and VHI. Correlation results between vegetation indices showed the highest correlation occurred between the vegetation index TCI and VHI with the potential for a medium drought of 0.501 and the potential for a high drought of 0.684. Also obtained are the results of the classification of 9 villages that fall into the category of high drought potential (High Risk). Accuracy results and Kappa values indicate that Random Forest is the best method used with a breakdown of values of 99.91% and 99.81%, respectively. Spatial prediction results are performed using Inverse Distance Weighted (IDW) on vegetation index and prediction. Testing of spatial relationships between villages that have the potential for drought is done using Moran s I. analysis.